2021
DOI: 10.3390/plants10071296
|View full text |Cite
|
Sign up to set email alerts
|

Four Centuries of Medicinal Mosses and Liverworts in European Ethnopharmacy and Scientific Pharmacy: A Review

Abstract: (1) Medicinal use of bryophytes dates to ancient times, but it has always been marginal due to their small size, difficult identification, lack of conspicuous organs which would attract attention (flowers, fruits) and insipid taste of the herb. The earliest testimonies of their medical use come from the 1500s. The interest in medicinal bryophytes diminished considerably in the 1880s, except for Sphagnum spp., which became a source of dressing material. The second half of the 20th century saw the revival of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…However, ethno-medicinal usage of this species has been reported from literature. In India and Canada, it is used to cure mouth and sore infections which indicate the presence of antimicrobial compounds that provide resistance against pathogens [25]. The results showed that a significant antibacterial activity was noted for the ethanol and methanol extract of R. hemisphaerica against both strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, ethno-medicinal usage of this species has been reported from literature. In India and Canada, it is used to cure mouth and sore infections which indicate the presence of antimicrobial compounds that provide resistance against pathogens [25]. The results showed that a significant antibacterial activity was noted for the ethanol and methanol extract of R. hemisphaerica against both strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are extensive data on the phytochemistry of some bryophyte species that support chemotaxonomy or have been motivated by potential agrochemical or human medical bioactive applications of the extracted compounds. Bryophytes have featured in traditional medicinal practices, with around 70 species having established uses ( Harris, 2008 ; Asakawa et al , 2013 a , b ; Martínez-Abaigar and Núñez-Olivera, 2021 ; Drobnik and Stebel, 2021 ). Bryophyte extracts have been demonstrated to be active against plant and human microbial pathogens; plant fungal pathogens and insect pests; and as allelopathic compounds ( Asakawa et al , 2013 a , b ; Commisso et al , 2021 ).…”
Section: Specialized Metabolite Pathways Of Bryophytesmentioning
confidence: 99%
“…It was applied to treat wounds, swelling, burns, and snake bites. Marchantia polymorpha L. was used as a medicine for inflammation, liver problems, bites and cuts, and as a diuretic [16,33], while Frullania tamarisci (L.) Dumort. was utilized as an antiseptic remedy [16].…”
Section: Ethnopharmacologymentioning
confidence: 99%
“…Funaria hygrometrica Hedw. served as a hemostatic to cure pulmonary tuberculosis, hematemesis, bruises, and athlete's foot dermatophytosis [33]. The moss Bryum argenteum Hedw.…”
Section: Ethnopharmacologymentioning
confidence: 99%
See 1 more Smart Citation